The Statistical Hypotheses Testing for Generalized Poisson Distribution - สุระพร บรรทม (KKU Science Journal, 2017)
By the theorem there exists a UMP test for testing hypotheses about the parameter of the generalized Poisson distribution. Neyman – Pearson lemma can be applied to find a test statistics for both a simple and a composite hypothesis. In addition, monotone likelihood ratio distribution as well as the properties of an exponential family will be taken into account in order to find a suitable test function for composite hypothesis.